Sistem Deteksi Posisi Objek Acak Berbasis Image Processing Pada Platform MyRIO - Alrynto Alrynto; Dahnial Syauqy; Fitri Utaminingrum (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Object recognition in this case position of random object is one of the main concern for development of computer science. Object recognition is very useful in another major implementation like maaping, industrial manufacturing, medical, security and many more. For implementation to another major, output of the system need to caliberate for that major. System output on this research are distance and slope value that have been caliberated into international value of length. This research try to develop object recognition using microcontroler by National Instrument MyRIO 1900 as image processor and webcam camera as optical sensor. The camera take object image from above of the object. System using image processing with Geometric Match Pattern method that match object image with template image geometrically and then will take data position and slope of the object. Output from image processing will show in the computer. In the testing will use one type of object in this case using reactangle and placed randomly. The testing will measure the function of the system for read object position, slope and manualization accuracy. Position test have percentage success 99.63% and slope test have percentage success 96.8%. Accuracy test using pixel tolerance and the highest accuracy 100% on 5 pixel tolerance.